Therapeutic Potential of Human Umbilical Cord-Derived Mesenchymal Stem Cells in Recovering From Murine Pulmonary Emphysema Under Cigarette Smoke Exposure - Chen, Xiao-Yue; Chen, Yi-Ying; Lin, Willie; Chen, Chien-Han; Wen, Yu-Chieh; Hsiao, Ta-Chih; Chou, Hsiu-Chu; Chung, Kian Fan; Chuang, Hsiao-Chi (Frontiers in Medicine, 2021)
Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) were shown to have potential for immunoregulation and tissue repair. The objective of this study was to investigate the effects of hUC-MSCs on emphysema in chronic obstructive pulmonary disease (COPD). The C57BL/6JNarl mice were exposed to cigarette smoke (CS) for 4 months followed by administration of hUC-MSCs at 3 × 106 (low dose), 1 × 107 (medium dose), and 3 × 107 cells/kg body weight (high dose). The hUC-MSCs caused significant decreases in emphysema severity by measuring the mean linear intercept (MLI) and destructive index (DI). A decrease in neutrophils (%) and an increase in lymphocytes (%) in bronchoalveolar lavage fluid (BALF) were observed in emphysematous mice after hUC-MSC treatment. Lung levels of interleukin (IL)-1β, C-X-C motif chemokine ligand 1 (CXCL1)/keratinocyte chemoattractant (KC), and matrix metalloproteinase (MMP)-12 significantly decreased after hUC-MSC administration. Significant reductions in tumor necrosis factor (TNF)-α, IL-1β, and IL-17A in serum occurred after hUC-MSC administration. Notably, the cell viability of lung fibroblasts improved with hUC-MSCs after being treated with CS extract (CSE). Furthermore, the hUC-MSCs-conditioned medium (hUC-MSCs-CM) restored the contractile force, and increased messenger RNA expressions of elastin and fibronectin by lung fibroblasts. In conclusion, hUC-MSCs reduced inflammatory responses and emphysema severity in CS-induced emphysematous mice.